Conjugated Microporous Polymers Doped with Rare Earth Ions: Synthesis, Characterization and Energy Transfer. Issue 8 (17th August 2020) - Cui, Di; Yao, Chan; Xu, Yanhong; Che, Guangbo
Abstract: In order to study the energy transfer between the conjugated polymer and rare‐earth ions, a series of conjugated microporous polymers (CMPs) CMP‐COOH@M (M=Eu 3+, Tb 3+, La 3+, and Sm 3+ ) with different kinds of rare‐earth ions was synthesized, in which the conjugated networks can effectively improve the luminescence of rare‐earth ions due to the effective energy transfer from the CMP network to the rare‐earth ions centers. The absolute quantum yield of CMP‐COOH ( Φ FL ) is 29.1 %, while the Φ FL value of CMP‐COOH@Eu, CMP‐COOH@Tb, CMP‐COOH@La, and CMP‐COOH@Sm is 9.4, 8.6, 14.3, and 9.1 %, respectively. This result indicates that the quantum efficiency of CMPs network is 1/2‐1/3 of the original one due to the coordination of rare earth ions, that is, rare‐earth ions can be recognized as fine modulators to adjust the emission color of CMPs in a controlled manner through controlling the species of rare‐earth ions. Abstract : A series of conjugated microporous polymers (CMPs) CMP‐COOH@M (M=Eu 3+, Tb 3+, La 3+, and Sm 3+ ) with different kinds of rare‐earth ions were synthesized, and the energy transfer between the conjugated polymer and rare‐earth ions was studied. The results indicated that rare‐earth ions can be used as fine modulators to tune the emission color of conjugated polymers in a controlled manner through controlling the species of rare‐earth ions. Xu, Che et al. report on synthesis, characterization and energy transfer in conjugated microporous polymers doped with rare earth ions